USING EXTENDED PORTFOLIO SELECTION IN INVESTMENT STRATEGIES - Ganbaatar, Narangoo; Chuluunbaatar, Ankhbayar (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study aims to determine the optimal investment portfolio based on the investor’s objective, expected return, risk tolerance, and investment cost. As a practical case study, we use quantitative data from 2013 to 2024 for six noncorrelated companies listed in Mongolian stock exchange’s Top 20 Index, including APU, Gobi, Makhimpex, Suu, Talkh Chikher, and Tavan Tolgoi. The optimization problem is formulated with the objective function of minimizing the risk per unit of return, subject to the following constraints: the expected return of the portfolio must be no less than 0.142, the level of portfolio risk does not exceed 0.062, and the initial investment cost modeled by a logistic distribution does not exceed 0.097. The optimal solution to this problem yields the following portfolio allocation: APU – 5.4%, Gobi – 6.8%, Makhimpex – 30.3%, Suu – 8.9%, Talkh Chikher – 28.4%, and Tavan Tolgoi – 20.2%. For this portfolio, the risk level is reduced by 26% compared to the initial value.